KEUANGAN DIGITAL BAGI GENERASI MUDA GMIM PETRA POOPOH WILAYAH TANAWANGKO: DIGITAL FINANCE FOR THE YOUNG GENERATION OF GMIM PETRA POOPOH, TANAWANGKO REGION (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Quality human resources are one of the factors that influence the lives of the younger generation, therefore the quality of human resources needs to be continuously improved, including their competencies, one of which is related to Digital Financial Literacy. Currently, digital financial literacy skills are not just a necessity, but have also become a lifestyle in the era of the Industrial Revolution 4.0. Restrictions on human movement during the Covid-19 pandemic have made digital transactions increasingly in demand and needed. The presence of digital financial services makes people or the younger generation have many options to access financial services without having to physically come to the office of a financial services institution. Offers, account openings, or purchases of financial products and services can be done digitally. The purpose of this program is to add and improve knowledge and skills regarding the benefits and risks of financial products and services, especially fraudulent investments and online loans (Pinjol). . The methods that can be applied to this Community partnership program are, Counseling, training and mentoring as well as evaluation. The expected output of this program is the publication of scientific journal articles and social media publications.